The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3758/s13415-012-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

rTMS stimulation on left DLPFC increases the correct recognition of memories for emotional target and distractor words

Abstract: According to a recent hypothesis, the prefrontal cortex has been proposed as the site of emotional memory integration, because it is sensitive to the recognition of emotional contents. In the present research, we explored the role of the dorsolateral prefrontal cortex (DLPFC) in memory recognition processes for positive versus negative emotional stimuli when old (target) and new (distractor, either semantically related or unrelated to the target) stimuli were presented. The role of the DLPFC was analysed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In addition, the PFC contribution in processing emotional interactions was confirmed by the hemodynamic and ERP profiles for both HH and HA. This result confirmed previous research which found that PFC plays a crucial role in the integration of different aspects of cognition, memory, and emotional regulation by managing the cognitive control over emotional stimuli and emotional behavior (Balconi and Ferrari 2012;Hariri et al 2000;Kalish and Robins 2006;Knight et al 1999;Miller and Cohen 2001). Therefore we may suggest a specific prefrontal cortical area may mediate the emotional processing by subjects who are observing inter-subjective interactions, independently from the human or not-human specificity of this interaction.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the PFC contribution in processing emotional interactions was confirmed by the hemodynamic and ERP profiles for both HH and HA. This result confirmed previous research which found that PFC plays a crucial role in the integration of different aspects of cognition, memory, and emotional regulation by managing the cognitive control over emotional stimuli and emotional behavior (Balconi and Ferrari 2012;Hariri et al 2000;Kalish and Robins 2006;Knight et al 1999;Miller and Cohen 2001). Therefore we may suggest a specific prefrontal cortical area may mediate the emotional processing by subjects who are observing inter-subjective interactions, independently from the human or not-human specificity of this interaction.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies provide evidence for the hypothesis called the "valence model", which states that withdrawal-related emotions are located in the right hemisphere whereas approach-related emotions are biased to the left hemisphere [36,38] . Focusing on the TMS technique, Balconi et al [39,40] found an increased facilitation of the retrieval of positive emotional cues (in terms of reduced response times) under stimulation of the left DLPFC during the retrieval phase. on the contrary, the memory performance relative to negative information was not influenced by left frontal stimulation.…”
Section: Episodic Memory and Tmsmentioning
confidence: 99%
“…Specifically, with regard to the development of an integrated sense of self and its representations in the future, mindfulness practice might have a positive effect on the activity of the dorsolateral prefrontal cortex, which is implicated in social perspective-taking, self-monitoring, emotional regulation, and coding of affective responses and emotionally-connoted information [54][55][56][57][58][59].…”
Section: The Mindfulness Approach: Implicit Responses Bodily and Sementioning
confidence: 99%